THE EFFECTIVENES OF SPELLING CITY WEBSITE IN IMPROVING ENGLISH SPELLING SKILL IN WRITING AMONG NINTH-GRADE STUDENTS AT SMPN 10 BARRU. - Fauziah, Nur; Aryana Akmal, Anugrah; Bulkis Maghfirah, Andi (JIPIS, 2025)
This study investigates the effectiveness of the Spelling City website in improving English spelling skills in writing among ninth-grade students at SMPN 10 Barru. Utilizing a Classroom Action Research (CAR) approach, the research was conducted over two cycles involving 27 students. Quantitative data were collected through pre-test and post-test evaluations, with improvements analyzed using N-gain scores. The findings reveal significant improvements in students' spelling skills, with average pre-test and post-test scores increasing notably between cycles. In Cycle I, students achieved a moderate level of improvement, while in Cycle II, more than 80% of students reached the desired competency level. This improvement highlights the potential of integrating technology-based tools, such as Spelling City, to create an engaging and interactive learning environment. Additionally, the study underscores the role of gamification, instant feedback, and adaptable word lists in motivating students and fostering sustained engagement. These elements not only enhance spelling accuracy but also contribute to better writing skills and greater learning enthusiasm. This research provides valuable insights into the use of web-based educational tools to address specific learning challenges, offering practical implications for teachers, policymakers, and developers of learning technologies.